IMPLEMENTATION OF CRITERION-REFERENCED ASSESSMENT IN ARABIC LANGUAGE EDUCATION MUSLIM CENDEKIA MALANG ELEMENTARY SCHOOL - Amelia, Fitri; Bahrun, Muhammad Farhan; Qomari, Nur (Abjadia : International Journal of Education, 2024)
This research falls under the category of descriptive qualitative research, aiming to systematically, realistically, and accurately uncover results by explaining each discovered aspect. The study focuses on understanding criterion-referenced assessment (CRA) and its application at Muslim Cendekia Batu Elementary School. The data in this research comprises primary and secondary data. Primary data were directly obtained from the research subjects, namely the Arabic language teachers at Muslim Cendekia Batu Elementary School, while secondary data were acquired from observations and document studies relevant to the research topic. Data collection was conducted through interviews and documentation. After data collection, the analysis was performed using descriptive analysis techniques according to Miles and Huberman. This technique involves three steps: (1) data reduction, which includes collecting, filtering, and systematically organizing data; (2) data display, which involves identifying meaningful patterns and relationships to draw conclusions; and (3) conclusion drawing or verification, which entails summarizing and verifying the results obtained from the analyzed data Criterion-referenced assessment (CRA) is a measurement method using specific standards where students are compared against predetermined standards within learning objectives. The purpose of CRA is to accurately measure the achievement of competencies set as success criteria, identifying what each individual has mastered and not mastered. CRA is applied in Arabic language learning at Muslim Cendekia Batu Elementary School through various methods, including project assessments and the results of daily tests and final exams.